LARANGAN PERNIKAHAN ANTARA DUA ORANG YANG BERINISIAL SAMA DI ACEH TIMUR - Hindun (Hukum Keluarga Islam IAIN LANGSA, 2018)
Marriage is an inner and outer bond between a man and a woman as a husband and wifewith the aim of forming a happy and eternal family or household based on the One Godhead. InGayo custom, marriage to the people of Seulemak Buket Village is still sacred with its customs,namely there are customary prohibitions on marriage between two people with the same initials, ifsomeone who wants to carry out a marriage is not permitted because it can cause havoc or chaos inthe household. Because researchers are interested in examining further the prohibition on suchmarriage.